Identify the types & reason of code mixing found in whatsapp group cargo department staff at ngurah rai airport - Muttaqien, Siti Rohmawati Imam; Sulatra, I Komang; Jendra, I Made Indrawan (Institut Pariwisata dan Bisnis Internasional, 2022)
The aims of this study are to find out (1) the types of code mixing found in WhatsApp Group cargo department by the staffs at Ngurah Rai Airport and (2) to analyse the reason of code mixing found in the WhatsApp Group by the staff at Ngurah Rai Airport. The data were taken from chat of cargo department staff in WhatsApp Group at Ngurah Rai Airport. The method of collecting data was starting from March 1 to 30, 2021. The analysis was done by applying descriptive qualitative method requires documentation to identify the types of code-mixing, purposed theory by Hoffman (1991) about the types of code mixing and the purposed reason of code-mixing theory from Holmes (2013). The result of this study shows that there two of three types that found in the WhatsApp Group cargo department by the staff at Ngurah Rai Airport, there are: Intra-sentential code mixing, intra-lexical code mixing and involvement in a change of pronunciation. The type of Intra-Sentential code-mixing was more commonly found in chat conversations by the staffs on WhatsApp group, who stated that it was easier not to change the language in the cargo world, which primarily used English, to keep it easier for interact and avoid misunderstandings in the handover of their assignments or job desks. Because this research is based on chat messages in a WhatsApp Group, types of involvement in a change in pronunciation can be identified because that type is part of speech. The reason of code-mixing purposed theory by Holmes (2013) there are four reasons, namely: Topic, participant, solidarity and status. Because the relationship between employees provided information about the duties being carried out between divisions, the topic became one of the most common causes for identifying code mixing in chat chats in WhatsApp groups by cargo department staff.